Correction: The evolution of bone-eating worm diversity in the Upper Cretaceous Chalk Group of the United Kingdom. - Sarah Jamison-Todd; James D Witts; Marc E H Jones; Deborah Tangunan; Kim Chandler; Paul Bown; Richard J Twitchett (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0320945.].